Cultural and Persuasive Da'wah: Building Harmony at the Blora Samin Community: Dakwah Kultural dan Persuasif: Membangun Harmoni pada Komunitas Samin Blora - Agus Riyadi; Nurbini (UIN Antasari Banjarmasin, 2026)
This study examines cultural and persuasive da’wah strategies in fostering harmony within the Samin (Sedulur Sikep) community in three remote villages in Blora Regency, Central Java, which is known for its resistance to conventional Islamic da’wah. Using a twelve-month qualitative ethnographic design, data were collected through participatory observation, in-depth interviews with 32 purposively selected informants, and document analysis. The findings reveal five effective cultural da’wah strategies: ‘pacelathon’ dialogues, the integration of values into slametan ceremonies, cross-community mutual aid, partnerships with traditional leaders, and cultural festivals that open up spaces for dialogue that were previously closed off. A persuasive ‘bil-hal’-based approach, in collaboration with traditional leaders, builds trust, strengthens internal openness within the Samin community, and fosters external harmony with the surrounding Muslim community. This research contributes to the Model of Inclusive Da’wah Based on Local Wisdom (MBKL), which is relevant to the management of diversity in Indonesia. KEYWORDS cultural preaching; persuasive preaching; Samin; local wisdom; Blora